PEMBEKALAN P3K CABANG BULUTANGKIS PADA GURU PJOK KECAMATAN TAMAN SARI JAKARTA BARAT - Khaeroni; Humaid, Hidayat; Apriyanto, Tirto (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Students are not required to excel, but the education unit (school) provides a forum for students to move freely and get to know and learn several sports, one of which is badminton. The learning process of PJOK, especially badminton material, is quite closely related to injuries. Like this, it is certainly very dangerous if an injury occurs to students, it can have a bad impact on their physical and mental well-being, especially for children at the elementary school (SD) education level because the child is still in the growth and development stage so it must be given. The solution offered from the above problems is to provide an understanding of P3K technical activities in the badminton branch for PJOK teachers and provide training and assistance in P3K technical activities in the badminton branch for PJOK teachers. Service activities are carried out by providing knowledge both theoretical and practical about PJOK teachers’ knowledge about P3K Badminton Branch Debriefing at PJOK Teachers, Taman Sari District, West Jakarta. Community service activities have been carried out well and received enthusiastic responses from the participants of the activity. This is evident from the participation rate of activity participants of 81.08% of the total PJOK teachers in Taman Sari District, West Jakarta. The level of satisfaction of PJOK teachers in Taman Sari District, West Jakarta, for this service activity is very high, which is 85.83%. Abstrak Peserta didik tidak dituntut untuk berprestasi namun satuan pendidikan (sekolah) memberikan wadah kepada peserta didik untuk keleluasaan bergerak serta mengenal dan belajar beberapa cabang olahraga salah satunya adalah cabang bulutangkis. Proses pembelajaran PJOK khususnya materi bulutangkis cukup erat kaitannya dengan cedera. Seperti hal ini tentu sangat berbahaya jika cedera terjadi kepada peserta didik, hal tersebut dapat berdampak buruk terhadap fisik dan juga mentalnya, apalagi untuk anak pada jenjang pendidikan Sekolah Dasar (SD) karena anak masih dalam tahap pertumbuhan dan perkembangan sehingga harus diberikan. Solusi yang ditawarkan dari permasalahan di atas adalah memberikan pemahaman kegiatan tehnis P3K pada cabang bulutangkis bagi guru-guru PJOK serta memberikan pelatihan dan pendampingan kegiatan tehnis P3K pada cabang bulutangkis bagi guru-guru PJOK. Kegiatan pengabdian dilakukan dengan pemberian pengetahuan baik teori maupun praktek tentang pengetahuan guru PJOK tentang Pembekalan P3K Cabang Bulutangkis Pada Guru PJOK Kecamatan Taman Sari Jakarta Barat. Kegiatan pengabdian kepada masyarakat telah terlaksana dengan baik dan mendapatkan respon yang antusias dari para peserta kegiatan. Hal ini terbukti dari tingkat partisipasi peserta kegiatan sebesar 81,08% dari total guru PJOK di Kecamatan Taman Sari Jakarta Barat. Tingkat kepuasaan guru PJOK Kecamatan Taman Sari Jakarta Barat terhadap kegiatan pengabdian ini sangat tinggi yaitu sebesar 85,83%. Kata Kunci: Guru PJOK, Sekolah Dasar, P3K